Estimation of a life table for the Peruvian national pension system - Valderrama Torres, José Artemio (2019)
A static life table is estimated using the nonparametric estimator proposed by Kaplan and Meier and the local polynomial regression technique for the graduation using more than 8 million administrative records collected during the years 2013 to 2017. The results reveal that the gap in life expectancy between men and women is lower than that reported by the current table. Thus, the diference in life expectancy measured at 65 years of age is reduced from seven to two years, explained by a decrease in the life expectancy of women of 2.4 years and an increase in life expectancy from 2.1 years in the case of men. The results also reveal that the net actuarial debt would be overestimated in S=2 billion compared to the officially estimated, this is the result of two opposing effects: a decrease in the reserve estimate in the case of women and an increase in the case of men, with the first effect dominating.